Preparation process and use method of electrochemical composite electrode
By using sandwich structure electrochemical composite electrode made of PVDF and conductive materials, combined with high-frequency vibration and heat treatment technology, the problems of short life and easy damage of the electrochemical electrode are solved, achieving higher current efficiency and electrocatalytic performance, significantly Improve the effect of circulating water treatment.
Patent Information
- Application Number
- CN202411268735.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-11
- Publication Date
- 2024-12-13
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
Existing electrochemical electrodes have short life and easy damage in circulating water treatment, resulting in reduced processing efficiency and high maintenance costs.
The sandwich structure electrochemical composite electrode is used to make a composite of polymer material PVDF and conductive material. By adjusting the applied voltage, high-frequency vibration of the electrode surface is caused to remove scale, and optimized heat treatment is carried out to improve electrocatalytic performance.
The service life of the electrode is extended to 6000 hours, the current efficiency and electrocatalytic performance are improved, the production costs are reduced, and the electrochemical efficiency is shown when dealing with high concentrations of organic pollutants.
Smart Images

Figure CN119118303A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field related to electrochemical electrode technology, and more specifically, particularly relates to a preparation process of an electrochemical composite electrode and a method for using the same. Background Art
[0002] Industrial circulating cooling water is widely used in industrial processes such as petrochemicals, electricity, steel, and chemicals, so it is also called circulating cooling water, accounting for more than 80% of the total industrial water consumption. With the repeated use and concentration of circulating water, the water quality gradually deteriorates, and the mineral concentration continues to increase, leading to scaling, corrosion, algae growth, and mud deposition. These problems will reduce the efficiency of the heat exchanger, waste energy, reduce the water flow cross-section, increase system resistance, and reduce water flow capacity, which may eventually lead to equipment damage, system shutdown, and high maintenance costs. Therefore, the circulating water must be effectively treated to ensure normal production and save water resources.
[0003] In recent years, electrochemical water treatment technology has received widespread attention as a more environmentally friendly treatment method than chemical agents. Electrochemical water treatment forms an alkaline environment near the cathode through electrolysis, making it easier for scaling substances to crystallize and precipitate. Near the anode, chloride ions generate free chlorine or hypochlorous acid, as well as hydroxyl radicals, oxygen radicals, ozone and hydrogen peroxide, which further enhance the sterilization and algaecide effects in the reaction chamber, and can even effectively eliminate microorganisms such as Legionella. The entire electrochemical process relies on the original substances of the water body and does not produce pollutants. It is a green and environmentally friendly water treatment process. Electrochemical water treatment can not only remove scaling elements and sterilize algae in water without the use of scale inhibitors, preservatives and slime strippers, but also increase the concentration rate of circulating water to more than 6 times, and the water saving rate exceeds 80%. For most make-up water qualities, after electrochemical treatment, the system discharge water contains almost no pollutants and has low operating costs.
[0004] The regeneration of electrochemical electrodes is the key to electrochemical treatment of circulating water technology. Currently, the main methods used are electrode reversal, mechanical scraping, and ultrasonic stripping. All of these methods may damage the electrodes and shorten their lifespan.
[0005] Therefore, in view of this, the existing structure and defects are studied and improved, and a preparation process and a method for using an electrochemical composite electrode are provided, in order to achieve a more practical and valuable purpose. Summary of the invention
[0006] In view of the above and / or existing problems of electrochemical electrodes in circulating water treatment, a preparation process and a method for using an electrochemical composite electrode are provided to overcome the above defects in the prior art.
[0007] The composite electrochemical electrode prepared by the method of the present invention is made of a polymer material PVDF (or P (VDF-TrFE)) with piezoelectric properties and a conductive material. The composite electrode has a sandwich structure, is firmly bonded to the matrix, and has excellent conductivity and piezoelectric properties. When used for circulating water treatment, the applied voltage can be easily adjusted to make the electrode surface vibrate at a microscale to remove the scale deposited on the surface, so that the electrode maintains a high current efficiency and improves the efficiency of water treatment.
[0008] The purpose and effect of the preparation process and use method of an electrochemical composite electrode of the present invention are achieved by the following specific technical means:
[0009] A process for preparing an electrochemical composite electrode, comprising:
[0010] S1: Weigh a certain amount of material according to the mass ratio of piezoelectric material to PVDF (or P (VDF-TrFE)) of 1:20 to 4:1, dissolve and disperse in a mixture of one or more polar organic liquids such as N, N-dimethylformamide, N, N-dimethylacetamide, or dimethyl sulfoxide, stir or ultrasonically disperse evenly, and prepare a PVDF (or P (VDF-TrFE)) solution with a mass percentage of 5 to 20%;
[0011] S2: Disperse the conductive material in the PVDF (or P (VDF-TrFE)) solution according to the conductive material: PVDF (or P (VDF-TrFE)) mass ratio of 1:20 to 10:1, and stir or ultrasonically disperse the conductive material evenly.
[0012] S3: Place the metal mesh flat on a glass plate and fix it with a clip, then pour the solution prepared in step 2 on the surface of the metal mesh, scrape it flat with a scraper, let it stand and dry, then pour the solution prepared in step 1 on its surface, let it stand and dry for use.
[0013] S4: stack another layer of metal mesh on the surface of the membrane prepared in step 3, then pour the solution prepared in step 2 on the surface of the metal mesh, scrape it flat with a scraper, and dry it naturally to obtain a composite electrode.
[0014] S5: heat treating the deposited composite electrode, the heat treatment process is as follows:
[0015] The electrode is heated to 500°C to 800°C at a heating rate of 5°C / min to 10°C / min under an inert gas protection or vacuum environment;
[0016] Maintain the temperature for 1 to 4 hours;
[0017] The mixture was cooled to room temperature at a cooling rate of 5°C / min to 8°C / min.
[0018] Furthermore, the piezoelectric material is one or a mixture of barium titanate, lithium tantalate, and lithium niobate.
[0019] Furthermore, the conductive material is one or a mixture of several of carbon nanotubes, graphene, carbon black and carbon fibers.
[0020] Furthermore, the metal mesh is made of a material selected from the group consisting of stainless steel mesh, copper mesh, titanium mesh, and nickel mesh.
[0021] Furthermore, the inert gas is argon or nitrogen.
[0022] Furthermore, the heat treatment temperature is 600° C. to 750° C. and is used for crystallization and performance optimization of the metal oxide electrocatalytic layer.
[0023] Furthermore, the insulation time is 2 hours, which is used to promote the uniform distribution of active materials and enhance the electrocatalytic performance of the electrode.
[0024] Furthermore, the heating rate is 5°C / min and the cooling rate is 8°C / min to ensure the stability of the composite electrode material and avoid thermal stress cracks.
[0025] Furthermore, after the heat treatment is completed, an anti-corrosion coating is coated on the surface of the electrode to further enhance the corrosion resistance of the electrode.
[0026] A method for using an electrochemical composite electrode, comprising:
[0027] When used for circulating water treatment, negative voltage is applied to both sides of the composite electrode and the electrode acts as a cathode.
[0028] When used for circulating water treatment, during the electrode regeneration stage, the voltage applied to both sides of the electrode is alternating current with a frequency of 0.1 to 100 MHz.
[0029] Compared with the prior art, the present invention has the following beneficial effects:
[0030] The composite electrode provided by the present invention has good electrical conductivity and mechanical properties, and when used as an electrochemical electrode, has high current efficiency and lifespan;
[0031] The composite electrode provided by the present invention has piezoelectric properties. By modulating the voltage applied to the electrode, the electrode can be made to vibrate at a high frequency, and the scale deposited on the surface can be peeled off and removed without damaging the electrode, so that the electrode maintains a high current efficiency.
[0032] The composite electrode provided by the present invention has low production cost, simple preparation method, and is easy to scale up to realize industrial production. Through the optimized heat treatment process, the electrocatalytic performance of the composite electrode in circulating water treatment is significantly improved. In the treatment of industrial wastewater containing high concentrations of organic pollutants, the electrode exhibits higher electrochemical efficiency and the service life is extended to 6000 hours, which is 20% longer than the service life of traditional electrodes. BRIEF DESCRIPTION OF THE DRAWINGS
[0033] In order to more clearly illustrate the embodiments of the invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying any creative work.
[0034] Figure 1 It is a schematic diagram of the structure of the composite electrochemical electrode of the present invention;
[0035] Figure 2 It is a wiring diagram of the composite electrochemical electrode of the present invention. DETAILED DESCRIPTION
[0036] The following embodiments of the present invention are described in further detail in conjunction with the accompanying drawings and examples. The following examples are used to illustrate the present invention, but are not intended to limit the scope of the present invention.
[0037] In the description of the present invention, unless otherwise specified, "plurality" means two or more than two; the orientations or positional relationships indicated by the terms "upper", "lower", "left", "right", "inner", "outer", "front end", "rear end", "head", "tail", etc. are based on the orientations or positional relationships shown in the drawings, and are only for the convenience of describing the present invention and simplifying the description, and do not indicate or imply that the device or element referred to must have a specific orientation, be constructed and operate in a specific orientation, and therefore cannot be understood as limiting the present invention. In addition, the terms "first", "second", "third", etc. are only used for descriptive purposes and cannot be understood as indicating or implying relative importance.
[0038] In the description of the present invention, it should be noted that, unless otherwise clearly specified and limited, the terms "connected" and "connection" should be understood in a broad sense, for example, it can be a fixed connection, a detachable connection, or an integral connection; it can be a mechanical connection or an electrical connection; it can be a direct connection or an indirect connection through an intermediate medium. For ordinary technicians in this field, the specific meanings of the above terms in the present invention can be understood according to specific circumstances.
[0039] As attached Figure 1 To Attachment Figure 2As shown:
[0040] A process for preparing an electrochemical composite electrode, comprising:
[0041] S1: Weigh a certain amount of material according to the mass ratio of piezoelectric material to PVDF (or P (VDF-TrFE)) of 1:20 to 4:1, dissolve and disperse in a mixture of one or more polar organic liquids such as N, N-dimethylformamide, N, N-dimethylacetamide, or dimethyl sulfoxide, stir or ultrasonically disperse evenly, and prepare a PVDF (or P (VDF-TrFE)) solution with a mass percentage of 5 to 20%;
[0042] S2: Disperse the conductive material in the PVDF (or P (VDF-TrFE)) solution according to the conductive material: PVDF (or P (VDF-TrFE)) mass ratio of 1:20 to 10:1, and stir or ultrasonically disperse the conductive material evenly.
[0043] S3: Place the metal mesh flat on a glass plate and fix it with a clip, then pour the solution prepared in step 2 on the surface of the metal mesh, scrape it flat with a scraper, let it stand and dry, then pour the solution prepared in step 1 on its surface, let it stand and dry for use.
[0044] S4: stack another layer of metal mesh on the surface of the membrane prepared in step 3, then pour the solution prepared in step 2 on the surface of the metal mesh, scrape it flat with a scraper, and dry it naturally to obtain a composite electrode.
[0045] S5: heat treating the deposited composite electrode, the heat treatment process is as follows:
[0046] The electrode is heated to 500°C to 800°C at a heating rate of 5°C / min to 10°C / min under an inert gas protection or vacuum environment;
[0047] Maintain the temperature for 1 to 4 hours;
[0048] The mixture was cooled to room temperature at a cooling rate of 5°C / min to 8°C / min.
[0049] Furthermore, the piezoelectric material is one or a mixture of barium titanate, lithium tantalate, and lithium niobate.
[0050] Furthermore, the conductive material is one or a mixture of several of carbon nanotubes, graphene, carbon black and carbon fibers.
[0051] Furthermore, the metal mesh is made of a material selected from the group consisting of stainless steel mesh, copper mesh, titanium mesh, and nickel mesh.
[0052] Furthermore, the inert gas is argon or nitrogen.
[0053] Furthermore, the heat treatment temperature is 600° C. to 750° C. and is used for crystallization and performance optimization of the metal oxide electrocatalytic layer.
[0054] Furthermore, the insulation time is 2 hours, which is used to promote the uniform distribution of active materials and enhance the electrocatalytic performance of the electrode.
[0055] Furthermore, the heating rate is 5°C / min and the cooling rate is 8°C / min to ensure the stability of the composite electrode material and avoid thermal stress cracks.
[0056] Furthermore, after the heat treatment is completed, an anti-corrosion coating is coated on the surface of the electrode to further enhance the corrosion resistance of the electrode.
[0057] A method for using an electrochemical composite electrode, comprising:
[0058] When used for circulating water treatment, negative voltage is applied to both sides of the composite electrode and the electrode acts as a cathode.
[0059] When used for circulating water treatment, during the electrode regeneration stage, the voltage applied to both sides of the electrode is alternating current with a frequency of 0.1 to 100 MHz.
[0060] The main purpose of heat treatment is to improve the electrocatalytic activity, mechanical strength and corrosion resistance of the composite electrode. By properly controlling the temperature and holding time, the structural stability of the electrocatalytic layer can be enhanced, and the crystallization of active materials such as metal oxides can be promoted, thereby improving the service life and stability of the electrode.
[0061] Embodiment 1:
[0062] Weigh 5g of nano-BaTiO3 and 200g of PVDF into a beaker, add 200mL of N,N-dimethylformamide, and disperse them evenly by ultrasonication to obtain solution A. Take 100mL of solution A, add 10g of carbon nanotube powder, and disperse them evenly by ultrasonication to obtain solution B. Place a 300-mesh stainless steel mesh with a size of 20cm×25cm flat on a glass plate, fix both ends with clips, then apply 20mL of solution B on the stainless steel mesh, scrape it flat with a scraper, let it stand and dry at room temperature, and after it is completely dried, apply 20mL of solution A on it again. After drying, place a layer of 300-mesh stainless steel mesh with a size of 20cm×25cm, then apply 20mL of solution B on the stainless steel mesh, scrape it flat with a scraper and dry it, and then obtain a composite electrochemical electrode. Then put the obtained composite electrode into a heat treatment furnace, and heat it to 650℃ at a rate of 5℃ / min under argon protection, and keep it at this temperature for 2 hours. During this period, the crystal structure formation of RuO2 and IrO2 is promoted to improve their electrocatalytic activity. After the insulation is completed, it is naturally cooled to room temperature at a rate of 8°C / min to ensure the stability of the electrode material structure and prevent cracks caused by thermal stress.
[0063] Embodiment 2:
[0064] Weigh 10g of nano-BaTiO3 and 200g of PVDF into a beaker, add 200mL of N,N-dimethylformamide, and disperse them evenly by ultrasonication to obtain solution A. Take 100mL of solution A, add 5g of carbon nanotube powder and 5g of graphene powder, and disperse them evenly by ultrasonication to obtain solution B. Place a 300-mesh stainless steel mesh with a size of 20cm×25cm flat on a glass plate, fix both ends with clips, then apply 20mL of solution B on the stainless steel mesh, scrape it flat with a scraper, let it stand and dry at room temperature, and after it is completely dried, apply 20mL of solution A on it again. After drying, place a layer of 300-mesh stainless steel mesh with a size of 20cm×25cm, then apply 20mL of solution B on the stainless steel mesh, scrape it flat with a scraper and dry it, and then obtain a composite electrochemical electrode. Then, put the obtained composite electrode into a heat treatment furnace, and heat it to 650℃ at a rate of 5℃ / min under argon protection, and keep it at this temperature for 2 hours. During this period, the crystal structure formation of RuO2 and IrO2 is promoted to improve their electrocatalytic activity. After the insulation is completed, it is naturally cooled to room temperature at a rate of 8°C / min to ensure the stability of the electrode material structure and prevent cracks caused by thermal stress.
[0065] How to use the electrode:
[0066] According to the attached Figure 2 When used for electrochemical treatment of circulating water, the voltages applied to both sides of the electrode through connections 1 and 2 are negative, and no voltage is applied to connection 3. The composite electrode is used as a cathode, and the current density is 40A·m-2 Electrolysis of water changes the local pH and converts Ca 2+ Mg 2+ The scale-forming ions are deposited on the electrode surface. After running for a period of time t1, disconnect the connection 2, and the programmed power supply applies high-frequency alternating current through the connection 1 and 3 for a period of time t2, so that the electrode surface vibrates and removes the scale deposited on the electrode surface. Under different t1 and t2 running times, the current changes after running for 24 hours are shown in Table 1.
[0067]
[0068] Specific use of the present invention:
[0069] The embodiments of the present invention are given for the purpose of illustration and description, and are not intended to be exhaustive or to limit the invention to the disclosed forms. Many modifications and variations will be apparent to those of ordinary skill in the art. The embodiments are selected and described in order to better illustrate the principles and practical applications of the present invention and to enable those of ordinary skill in the art to understand the present invention and thereby design various embodiments with various modifications suitable for specific uses.
Claims
1. A process for preparing an electrochemical composite electrode, characterized in that: include: S1: Weigh a certain amount of material according to the mass ratio of piezoelectric material to PVDF (or P (VDF-TrFE)) of 1:20 to 4:1, dissolve and disperse in a mixture of one or more polar organic liquids such as N, N-dimethylformamide, N, N-dimethylacetamide, or dimethyl sulfoxide, stir or ultrasonically disperse evenly, and prepare a PVDF (or P (VDF-TrFE)) solution with a mass percentage of 5 to 20%; S2: Disperse the conductive material in the PVDF (or P (VDF-TrFE)) solution according to the conductive material: PVDF (or P (VDF-TrFE)) mass ratio of 1:20 to 10:1, and stir or ultrasonically disperse the conductive material to make it uniform; S3: Place the metal mesh flat on the glass plate and fix it with a clip, then pour the solution prepared in step 2 on the surface of the metal mesh, scrape it flat with a scraper, let it stand and dry, then pour the solution prepared in step 1 on the surface, let it stand and dry for later use; S4: stacking a layer of metal mesh on the surface of the membrane prepared in step 3, then pouring the solution prepared in step 2 on the surface of the metal mesh, scraping it flat with a scraper, and drying it naturally to obtain a composite electrode; S5: heat treating the deposited composite electrode, the heat treatment process is as follows: The electrode is heated to 500°C to 800°C at a heating rate of 5°C / min to 10°C / min under an inert gas protection or vacuum environment; Maintain the temperature for 1 to 4 hours; The mixture was cooled to room temperature at a cooling rate of 5°C / min to 8°C / min.
2. The process for preparing an electrochemical composite electrode according to claim 1, characterized in that: The piezoelectric material is one or a mixture of barium titanate, lithium tantalate, and lithium niobate.
3. The process for preparing an electrochemical composite electrode according to claim 1, characterized in that: The conductive material is one or a mixture of carbon nanotubes, graphene, carbon black and carbon fibers.
4. The process for preparing an electrochemical composite electrode according to claim 1, characterized in that: The metal mesh is made of a stainless steel mesh, a copper mesh, a titanium mesh, or a nickel mesh.
5. The process for preparing an electrochemical composite electrode according to claim 1, characterized in that: The inert gas is argon or nitrogen.
6. The process for preparing an electrochemical composite electrode according to claim 1, characterized in that: The heat treatment temperature is 600° C. to 750° C. and is used for crystallization and performance optimization of the metal oxide electrocatalytic layer.
7. The process for preparing an electrochemical composite electrode according to claim 1, characterized in that: The insulation time is 2 hours, which is used to promote the uniform distribution of active materials and enhance the electrocatalytic performance of the electrode.
8. The process for preparing an electrochemical composite electrode according to claim 1, characterized in that: The heating rate is 5°C / min and the cooling rate is 8°C / min to ensure the stability of the composite electrode material and avoid thermal stress cracks.
9. The process for preparing an electrochemical composite electrode according to claim 1, characterized in that: After the heat treatment is completed, an anti-corrosion coating is applied on the surface of the electrode to further enhance the corrosion resistance of the electrode.
10. A method for using an electrochemical composite electrode, characterized in that: include: When used for circulating water treatment, negative voltage is applied to both sides of the composite electrode, and the electrode acts as a cathode; When used for circulating water treatment, during the electrode regeneration stage, the voltage applied to both sides of the electrode is alternating current with a frequency of 0.1 to 100 MHz.
Citation Information
Cited By
Titanium electrode group for wastewater treatment and application thereof
CN119774720A
